Blocking the FKBP12 induced dendrimeric burst in aberrant aggregation of α-synuclein by using the ElteN378 synthetic inhibitor - Gabriella Caminati; Maria Raffaella Martina; Stefano Menichetti; Piero Procacci (Taylor & Francis Group, 2019)
α-Synuclein (α-syn), a disordered cytoplasmatic protein, plays a fundamental role in the pathogenesis of Parkinson's disease (PD). Here, we have shown, using photophysical measurements, that addition of FKBP12 to α-syn solutions, dramatically accelerates protein aggregation, leading to an explosion of dendritic structures revealed by fluorescence and phase-contrast microscopy. We have further demonstrated that this aberrant α-syn aggregation can be blocked using a recently discovered non-immunosuppressive synthetic inhibitor of FKBP12, ElteN378. The role of FKBP12 and of ElteN378 in the α-syn aggregation mechanism has been elucidated using molecular dynamics simulations based on an effective coarse-grained model. The reported data not only reveal a new potent synthetic drug as a candidate for early stage treatment of α-syn dependent neurodegenerations but also pave the way to a deeper understanding of the mechanism of action of FKBP12 on α-syn oligomeric aggregation, a topic which is still controversial.